Analysis of the Represented Interior Space: Hermeneutic Study of the Peres Maldonado Ex-voto - de León, Blanca Ruiz Esparza Díaz; Gonzaléz Romo, Héctor Omar (UI Scholars Hub, 2025)
The paper demonstrates the application of Henri Lefebvre's postulates in the hermeneutical study of the Peres Maldonado Ex-voto, created in Aguascalientes in 1777. This piece, authored by an unknown artist, likely illustrates the first mastectomy performed in Mexican lands. This study employs an analytical framework that integrates the propositions made by the philosopher Henri Lefebvre and the experiential spatial systems proposed by the authors. The former formulates a conceptual foundation that unfolds the body in three spatial dimensions: mental, physical, and social. The unfolding could make possible the defragmentation of the painting's elements to analyse the concept of corporeality or total body, as mentioned by Lefebvre. Subsequently, the experiential spatial systems complement the spatial analysis through relational concepts consisting of body-mind, body-gestures, body-attire, body-objects, and body-interior/exterior envelope. The analysis offers some new insights into several components of the simulated pictorial space of the voting offering, including the principal female figure, the secondary characters, the gestures and postures, attire, objects, furnishings, and constructed interior environment. The findings contribute to the development of new methodologies for interpreting spatial configuration in artistic works and, consequently, offer significant advancements in the fields of interior architectural space design and art.